Long Term Behaviour of Fibrous Concrete Composite (FCC): A Conspectus - Jamaludin, Mohamad Yatim; Ogunbode, Ezekiel Babatunde; Ishak, Mohd. Yunus; Abeku, Deri Mamman; Razavi, Meisam (Journal of Advanced Research in Applied Mechanics, 2020)
Fibrous concrete composite (FCC) have been applied in numerous civil engineering structures, such as pavements, dams, runway, hydraulic structures, aircraft parking, and runway. The desire for their usage as being due to their unique properties compared with other materials. The stability of fibres in cement concrete appears to be good enough, but further long term tests are necessary to evaluate their durability and performance under mechanical sustained load. This is owing to the dearth in knowledge on the fibrous concrete particularly bio fibrous concrete composites (BFCC) behaviour and response to compressive, flexural and uniaxial tensile sustained loads. Therefore, an in-depth study into the creep performance of BFCC is necessitated to understand the long term behaviour of this biodegradable and environmental friendly construction product. This will avail the structural engineers and builders’ adequate understanding and data for design construction purpose of this green concrete product.